Efektivitas Peran Pejabat Pengelola Informasi Dan Dokumentasi (PPID) Dalam Meningkatkan Keterbukaan Informasi Publik di KPU Kabupaten Karangasem - Ni Made Lestari; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2023)
Openness of public information is a means of optimizing public supervision of the performance of an institution. PPID is a means to make it easier for the public to obtain the information they need. There are problems related to the effectiveness of the role of PPID which is not yet fully effective, this condition is the background for this research in order to find out the effectiveness, obstacles and efforts made to increase the effectiveness of the role of Information and Documentation Management Officers in increasing information openness in the Karangasem Regency KPU. This research uses a qualitative descriptive method approach. The aim of the research is to determine and analyze the effectiveness of the role of Information and Documentation Management Officers in increasing information transparency in the Karangasem Regency KPU. The research results show that the role of Information and Documentation Management Officers in increasing public information openness in the Karangasem Regency KPU, seen from the indicators of achieving goals, is effective, but seen from the integrity and adaptation indicators, it is not yet fully effective. The obstacles are that the service space is not representative enough, there is still a lack of human resources capable of managing PPID, the budget availability to socialize PPID is inadequate and the infrastructure for website-based e-PPID is inadequate. The efforts made include efforts to disseminate information through socialization both directly and online, fulfill the shortage of human resources and improve the quality of website-based e-PPID infrastructure so that it functions optimally.